2018
DOI: 10.1186/s12889-018-5621-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of job insecurity on long-term self-rated health – results from the prospective population-based MONICA/KORA study

Abstract: BackgroundJob insecurity has been associated with impaired self-rated health (SRH) in cross-sectional studies, but prospective findings with short, medium and long-term follow-up yielded mixed findings. Therefore, the aim of the present study was to assess the long-term association between perceived job insecurity and SRH, after controlling for baseline levels of health status and life-style choices. Furthermore, three different follow-up periods (14, 19 and 24 years) were considered.MethodsData were derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…The survival, advancement and competitiveness of organisations in the turbulent labour market depend on an organisation's ability to effectively manage the challenges brought about by change, both in the internal and external environment (Sartori & Rolandi, 2013). Barrech, Baumert, Gündel, and Ladwig (2018) mentioned that optimisation and reorganisation initiatives to deal with challenges are becoming more frequent.…”
Section: Introductionmentioning
confidence: 99%
“…The survival, advancement and competitiveness of organisations in the turbulent labour market depend on an organisation's ability to effectively manage the challenges brought about by change, both in the internal and external environment (Sartori & Rolandi, 2013). Barrech, Baumert, Gündel, and Ladwig (2018) mentioned that optimisation and reorganisation initiatives to deal with challenges are becoming more frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent economic crises in recent decades have created concern for the global economic situation and led to a deterioration in the work environment worldwide. Reforms and reorganizations are becoming a frequent occurrence (Barrech, Baumert, Gündel, & Ladwig, 2018). Employees increasingly worry about whether they will be able to retain their job, thus creating a sense of job insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…White race, female gender, young age, high educational attainment, being married, and having a full-time job were associated with better subjective health and happiness. Other studies have shown that subjective health and happiness, two key elements of human well-being, are affected by educational level 7,32,33 , marital status 7,33,34 , and income 7,[32][33][34][35] . Other determinants of these measures include gender 7,32,33,36 , age 13,[32][33][34] , race [37][38][39][40] , culture 34,41 , social support 7,34 , and even genetics 36,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it is expected from men to support their families and be the breadwinners; however, this pattern is more crucial in more traditional societies 53 . It is not only having a job, but having a secure job which is an important determinant of subjective health and happiness 35 .…”
Section: Discussionmentioning
confidence: 99%